2008
DOI: 10.1002/mrm.21608
|View full text |Cite
|
Sign up to set email alerts
|

Improving the pharmacokinetic parameter measurement in dynamic contrast‐enhanced MRI by use of the arterial input function: Theory and clinical application

Abstract: One of the most powerful features of the dynamic contrastenhanced (DCE) MRI technique is its capability to quantitatively measure the physiological or pathophysiological environments assessed by the passage of contrast agent by means of modelbased pharmacokinetic analysis. The widely used two-compartment pharmacokinetic model developed by Brix and colleges fits tumor data well in most cases, but fails to explain the biexponential arterial input function. In this work, this problem has been attacked from a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…A substantial effort has been made by many investigators to improve the reliability of the PMPs, and a wealth of correction algorithms is proposed to improve the AIF calculation [15][16][17][18][19], or tissue input data [20,21]. Alternative algorithms to improve the model [22] have also been proposed.…”
Section: Introductionmentioning
confidence: 98%
“…A substantial effort has been made by many investigators to improve the reliability of the PMPs, and a wealth of correction algorithms is proposed to improve the AIF calculation [15][16][17][18][19], or tissue input data [20,21]. Alternative algorithms to improve the model [22] have also been proposed.…”
Section: Introductionmentioning
confidence: 98%
“…The contrast agent in the intravascular space is ignored. A represents the distribution volume (the extravascular extracellular space) of the contrast agent in the tissue, if the relaxivity, the native T1, and the dose do not vary signifi cantly (30)(31)(32). The effl ux rate constant, K ep (expressed as per minute), refl ects the contrast agent transit between the extravascular and intravascular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the variability associated to the AIF selection [80,[124][125][126][127][128]. Three different approaches are commonly taken:…”
Section: Arterial Input Functionmentioning
confidence: 99%